Innovation and Cooperation Networks in Hungary - Csizmadia, Zoltán; Grosz, András (Discussion Papers, 2022)
In our time recognising the necessity and values (benefits) of cooperation together with building, maintaining and developing cooperation systems are the essential prerequisites of competitiveness and innovative skills. After taking the initial steps, Hungarian research on inter-organisational networks and institutional partnerships did not achieve a sufficient ‘critical mass’ to turn into the subject of broader and deeper comparative studies. Nevertheless, the idea of a national innovation system, regional innovation systems, and their realisation in innovation policy are increasingly in need of nationwide empirical social science research; to investigate the collaborative willingness and the concrete cooperative activities of the actors of the innovation system as well as to study the degree of organisation and structure of economic and development networks. In recent years, inquiries have typically been conducted in certain regions to map the innovation activities of enterprises and their cooperation systems or they attempted to explore the interconnection between cooperation and innovation capacity on a regional-level sample. In addition, research approaching the problem from the other side, investigated rather inter-firm contacts and cooperation forms without any regard to the issues of innovation and innovation activities. Our research project comprises a questionnaire-based, representative, nationwide survey which was conducted among Hungarian small and medium-sized enterprises to serve as a basis for presenting the characteristics of the innovative capacities of firms, the social network parameters of economic and innovation partnerships, the patterns of the sectoral and regional differences and the set of motivating and inhibiting factors of cooperation. This paper summarises the first results of research basically with descriptive purposes, so that the basic pattern of the main corporate properties related to the two main topics could clearly be identified. Thus, it can also be considered as an initial diagnosis focusing on certain important factors of the competitiveness of Hungarian economy, and aims to provide empirically-based, up to date information.